S. marcescens sepsis with brain involvement: a fatal outcome - Sofia Aires; Simão Frutuoso; Carmen Carvalho (Hygeia Press di Corridori Marinella, 2016)
A growth restricted 30-week premature girl was admitted to the Neonatal Intensive Care Unit (NICU) with respiratory distress. In spite of a favorable respiratory evolution, she had a nosocomial sepsis at day 18. She was initially started on gentamicin and vancomycin, and then switched to meropenem due to clinical deterioration and a positive blood culture for S. marcescens. Brain ultrasound, initially only with a transitory periventricular echodensity, showed several echogenic foci throughout all parenchyma, strongly sug- gesting brain abscess. Hemodynamic and neurologic worsening ensued with a fatal outcome on day 21. S. marcescens is a Gram-negative bacterium frequently associated with infections. The occurrence of brain involvement, with abscess formation, greatly worsens the prognosis. This case report illustrates the severity of neonatal sepsis by Serratia spp., documented by extensive brain involvement leading to a fatal outcome, despite a prompt and adequate therapy.